Influence on the delamination phenomenon of matrix type and thermal variations in unidirectional carbon‐fiber epoxy composites. Issue 4 (4th April 2014) - Coronado, Patricia; Argüelles, Antonio; Viña, Jaime; Bonhomme, Jorge; Mollón, Victoria
Abstract : This article analyzes the influence of temperature on the delamination phenomenon in two composites with the same carbon‐fiber reinforcement, but different epoxy matrices. Interlaminar crack initiation and propagation under Mode I with static and fatigue loading are experimentally assessed for different test temperatures: 20, 50, and 90°C. The materials under study are made of AS4 unidirectional carbon fibers and different matrices: one is made of a 3501‐6 epoxy matrix (AS4/3501‐6), whereas the other is made of an 8552 epoxy matrix modified to increase its toughness (AS4/8552). Both composites have a symmetric laminate configuration [0°]16s . In the experimental program, double cantilever beam specimens were tested under static and fatigue loading. A fractographic study was also performed using a scanning electron microscope on samples obtained from specimens previously tested under static and fatigue loading. A comparison was made of the fracture surfaces at the different test temperatures and the experimental tests' results obtained. POLYM. COMPOS., 36:747–755, 2015. © 2014 Society of Plastics Engineers